PHYSICAL FITNESS STUDENTS 10-12 YEARS, GORONTALO CITY - Syarif Hidayat (Universitas Negeri Gorontalo, 2019)
The purpose of this study was to determine the level of physical fitness of students aged 10-12 years in Gorontalo City. This type of research is survey research. The population in this study amounted to 18,814 students from 116 Elementary Schools while a sample of 1789 students from 18 schools was taken using a cluster sampling technique. Data collection techniques used to test and measurement techniques. The instrument used to measure physical fitness uses the TKJI Test instrument 2010. Data analysis techniques in this study used the standard physical fitness norms of TKJI to measure the level of physical fitness of students. The results showed that there were 0 students or 0% in the excellent classification, there were 19 students or 1% in the good classification, there were 267 students or 15% in the middle classification, there were 1432 students or 80% in the less classification, there were 71 students or 4% in the classification less. Thus it can be concluded that students aged 10-12 years in Gorontalo City level of physical fitness are in poor condition.